Profitability measures of dairy cows - Ribeiro, Anamaria Cândido; McAllister, Alan Jackson; Queiroz, Sandra Aidar de [UNESP] (FapUNIFESP (SciELO), 2008)
This study was aimed at defining profitability measures designed for prediction of breeding values (EBV) in dairy cows. Performance and economic data recorded in herds enrolled in the DHIA (Dairy Herd Improvement Association) program in Kentucky, USA, were used to evaluate economic functions which included the following profitability measures: lifetime net income (LNI), efficiency (EF), milk income over feed costs (IOFC), net income per day of productive life (NIPL), net income at the end of the first lactation (NI1), and milk income over feed costs at the end of the first lactation (IOFC1). The estimated averages for LNI, EF, IOFC, NIPL, NI1 and IOFC1 were respectively US$ 532.13, 1.04, US$ 3038.19, US$ -0.16, US$ -69.34 and US$ 1293.77. The heritability estimates for these traits ranged from 0.06 to 0.09. The EBV and Spearman correlation estimates were positive, ranging from moderate to high values, suggesting a direct linear relationship among the profitability measures. LNI was the best profitability measure and genetic correlation estimates between LNI and economic measures recorded in first lactation (NI1 and IOFC1) were moderate (<0.56). NI1 was the most efficient profitability measure, but it would be easier to record data to calculate IOFC1. Overall, results do not suggest any economic function measured in the first lactation as a selection criteria for LNI. The profitability measures were affected by the short productive life of the animals in the herds. Selection based on different profitability measures would not result in similar ranking of sires. © 2008 Sociedade Brasileira de Zootecnia.
Keywords: Efficiency; Holstein; Lifetime income; Milk yield; Animalia; Bos; Human herpesvirus 4